BIOECOLOGY AND IMPORTANCE OF HALOXYLON AND SALSOLA SPECIES FROM THE CHENOPODIACEAE FAMILY DISTRIBUTED AROUND NUKUS CITY IN THE KYZYLKUM DESERT (Modern American Journal of Biological and Environmental Sciences, 2025)
The Kyzylkum Desert is one of the largest deserts in Uzbekistan, located between the Amu Darya and Syr Darya rivers. The areas around Nukus city, particularly in the northwestern part of the Republic of Karakalpakstan, occupy a significant portion of this desert. Here, species of Haloxylon (saxaul) and Salsola (saltwort) belonging to the Chenopodiaceae family (now part of Amaranthaceae) are widespread. These plants form the main component of the desert ecosystem and are highly adapted to desert conditions. This article details the bioecology, distribution, and importance of these species.